2001
DOI: 10.1520/jfs15017j
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the AmpFℓSTR™ Profiler Plus PCR Amplification Kit for Use in Forensic Casework

Abstract: According to TWGDAM guideline 4.5 (1), prior to implementing a new DNA analysis procedure or an existing DNA analysis procedure developed by another laboratory, the forensic laboratory must first demonstrate reliability of the procedure inhouse. Seven phases were designed to validate the use of the AmpFᐉSTR Profiler Plus PCR Amplification Kit, as well as the PE Applied Biosystems 310 Genetic Analyzer. This report summarizes the results obtained for each of the seven phases of the validation study which include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 8 publications
2
13
0
Order By: Relevance
“…The precision evaluation was performed as described previously [5,10,11]. DNA sequencing was performed for novel STRs, novel alleles, off-ladder alleles, and loci with limited sequence data using methods described previously [5].…”
Section: Methodsmentioning
confidence: 99%
“…The precision evaluation was performed as described previously [5,10,11]. DNA sequencing was performed for novel STRs, novel alleles, off-ladder alleles, and loci with limited sequence data using methods described previously [5].…”
Section: Methodsmentioning
confidence: 99%
“…STR typing typically involves a polymerase chain reaction (PCR) amplification step followed by size fractionation of the resulting products and fluorescent signal detection and processing. Numerous studies have shown that the signal associated with each allele of a heterozygote at a given locus is approximately equal [3][4][5][6][7][8][9]. General practice has shown that the peak height ratio, as measured by dividing the height (in relative fluorescent units (RFUs)) of the lower quantity allele by the height of the higher quantity allele "should be greater than approximately 70% in a single source sample" [3].…”
Section: Introductionmentioning
confidence: 99%
“…The precision of PCR fragments were assessed using three selected donor DNA samples (A, B, and C) and three control DNA samples (9947A, GM9948, and GM3657) among each locus especially those that exhibited the following characteristics: (1) the shortest fragment (102 base, D21S1437, allele 7) and the longest fragment (455 base, Penta D, allele 18), (2) alleles that differ in size by one or two bases (D18S1270, alleles 9.1 and 9.2; D22S683, alleles13.2, 14, and 14.2), and (3) "n" and "n±1" alleles. Precision was calculated as the standard deviation (SD) of size estimated as described previously [16,17].The bins for the GeneMapper software and the category boundaries for the Genotyper were derived from the resulted SD.…”
Section: Methodsmentioning
confidence: 99%